2020
DOI: 10.1002/batt.202000240
|View full text |Cite
|
Sign up to set email alerts
|

Computational Design of Ductile Magnesium Alloy Anodes for Magnesium Batteries

Abstract: The main advantage of Mg batteries over other metal counterparts is its ability to work with a pure metallic anode, achieving a very high specific capacity. Unfortunately, pure Mg is hard to machine due to its brittleness, making it extremely difficult to produce foils that are thin enough for practical battery applications. Alloying Mg with small amounts of doping elements can enhance its ductility. However, care should be given to ensure that the dopants do not interfere with the electrochemical process of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…On the other hand, another challenge is the poor mechanical properties of pure Mg foils caused by its limited intrinsic ductility [102], brittleness and mechanical weakness, especially for ultrathin foils (<100 µm) [103]. However, to obtain high specific energy Mg batteries, it is mandatory to use thin Mg metal foils anodes (15 µm), by means of Mg alloys [103][104][105].…”
Section: Current and Future Challengesmentioning
confidence: 99%
“…On the other hand, another challenge is the poor mechanical properties of pure Mg foils caused by its limited intrinsic ductility [102], brittleness and mechanical weakness, especially for ultrathin foils (<100 µm) [103]. However, to obtain high specific energy Mg batteries, it is mandatory to use thin Mg metal foils anodes (15 µm), by means of Mg alloys [103][104][105].…”
Section: Current and Future Challengesmentioning
confidence: 99%
“…81 However, a recent computational study focused on cast alloys, which have good processibility and thus scalability, reported that only a few of the studied elements were beneficial for the electrochemical process of plating and stripping. 100 Besides, Yang et al collected several studies which reported the influence of microstructure and composition of Mg alloys on their mechanical properties, ductility, and strength. These kinds of properties might profoundly affect the performance of different alloy anode materials for RMB.…”
Section: Anodesmentioning
confidence: 99%
“…However, the poor ductility of the pure Mg metal makes it challenging to produce very thin Mg electrodes. 247,248 Maddegalla et al demonstrated the viability of manufacturing ultrathin Mg anodes (B25 mm thickness) in electrochemical cells by using AZ31 Mg alloys (3 wt% for Al, 1 wt% for Zn, and 96 wt% for Mg). 249 Despite the use of the alloyed anode, the AZ31 Mg alloy thin foil anodes exhibited electrochemical behaviours comparable to pure Mg foil anode (B100 mm thickness) during the Mg stripping and deposition process.…”
Section: Anodes In Mg-ion Batterymentioning
confidence: 99%